Development of wireless vertical bar spinner combat robot - Amirul Syafiq Sadun; Jamaludin Jalani; Suziana Ahmad; Amiera Saryati Sadun; Sumaiya Mashori (Institute of Advanced Engineering and Science, 2020)
Recently, combat robot competition has become one of the most famous engineering competitions among schools and universities. The robots are usually built with a destructive weapon, which can immobilize or disable opponent’s robot and win the match. Despite the variety of robot design and concept, the trend has shown that most of the local contestant tend to design a horizontal axis weapon type. In this project, a wireless vertical axis bar spinner combat robot is designed and developed for the 3rd Malaysia Combat Robot Competition which was held at National Science Centre (PSN) in 2017. The robot is controlled using radio control (RC) and powered by a highly discharge 22.2V Lithium Polymer (LiPo) chemical battery. Furthermore, related analysis has been conducted to meet the design and performance requirement of the competition. With the DC brush motor and thick metal bar rotating in vertical axis, the robot has proven to produce high power, torque and speed during the competition.